The City of God Books VI & VII. - Augustinus, Aurelius sanctus 354-430; Walsh, P. G. (Patrick Gerard) (Warminster Aris and Phillips, 2010)
This edition of "St Augustine's City of God" is the only one in English to provide a text and translation as well as a detailed commentary of this most influential document in the history of western Christianity. In these books, written in the aftermath of the sack of Rome in AD 410 by the Goths, Augustine replies to the pagans, who attributed the fall of Rome to the Christian religion and its prohibition of the worship of the pagan gods. Books VI and VII focus on the figure of Terentius Varro a man revered by Augustine's pagan contemporaries. By exploiting Varro's learned researches on Roman religion, Augustine condemns Roman religious practices and beliefs in order to refute pagan claims that the Roman deities had guaranteed a blessed life in the hereafter for their devotees. These books are therefore not only an invaluable source for the study of early Christianity but also for any student of Classical Rome, who is provided here with a detailed account of one of the most learned figures of Roman antiquity one whose own works have not survived in the same state.